Supervising Academic Athletic Counseling - Anderson, Mark B.; Van Raalte, Judy L. (My University, 1994)
There has been much discussion in the academic athletic counseling literature about "how to" deliver services to various populations. However, little attention has been devoted to the "quality control" of these services. One important way of maintaining service quality is through the supervision of academic athletic counselor trainees and practitioners. The purpose of this article was twofold: first, to present supervision models particularly pertinent to the field of academic athletic counseling; and second, to present issues and problems commonly encountered in the supervision of academic athletic counselor trainees and practitioners.
Keywords: supervision; academic support; models